PERAN GIBEI SEBAGAI MEDIA EDUKASI PASAR MODAL BAGI MAHASISWA UNIVERSITAS HASYIM ASY’ARI - Kharimatus Sholikha; Peni Haryanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The low level of capital market literacy among university students highlights the need for effective educational media, one of which is provided through GIBEI Unhasy. This study aims to analyze the role of GIBEI in enhancing students’ understanding of the capital market and to identify the challenges encountered in its implementation. The research employed a descriptive qualitative method through interviews, observations, and documentation. The findings indicate that GIBEI’s educational programs such as seminars, training sessions, trading simulations, and the Capital Market School (SPM) in collaboration with OJK, BEI, and Phintraco Sekuritas effectively improve students’ understanding of basic concepts, transaction mechanisms, and investment analysis, as reflected in the increasing number of students opening securities accounts. Overall, GIBEI Unhasy plays a significant role in strengthening students’ capital market literacy, although several challenges remain, including differences in initial understanding, limited time availability, and resource constraints among the organizers.